Elaboración de menús de alimentos nutritivos - Fauta Villarroel, María Fernanda (2016)
This research project's main aim is to develop different kinds of nutritious menus for children "Luis Fernando Vivero" School so that infants improve the quality of their daily diet by eating nutritious foods that allow them to have a better both social development and cognitive, in many educational institutions can demonstrate a lack of knowledge and training of the educational community in general about the importance of a healthy diet for the integral development of children, it is for this reason that intends to carry out an investigation to determine the degree of knowledge of teachers and parents about nutritious food and the application of it in the daily lives of school children "Luis Fernando Vivero". It is necessary that parents also know the benefits and the benefits of good nutrition for their small to provide the necessary nutrients for infants have the energy to develop each of the activities of their school day. The main beneficiaries dl project were children of the school "Luis Fernando Vivero" because based on the information and training generated can exponentially improve the quality of food they eat and improve their growth and development as well as enjoying a good health, eating nutritious foods promotes growth and development both physically and mentally children of our society. The aim pursued long-term project is to generate a food culture that allows exponentially improve the quality of life of society in general, since the habits acquired during the first years back will remain and be strengthened in the later stages of life to reach adulthood and then will play in future generations.